Risk Factors of Filariasis in Brebes Regency (Universitas Negeri Semarang, 2020)
Filariasis or elephantiasis is an infectious disease affecting lymph nodes (lymph nodes) caused by filarial worms and transmitted by various species of mosquitoes. Brebes Regency is an area with the highest cases of Filariasis in Central Java Province. The number of cases of Filariasis until 2018 there were 65 patients. In addition, the discovery of new cases in the past two years has increased exactly in 2018 by 5 cases to 8 cases in 2019. The purpose of the study was to analyze the risk factors for the incidence of filariasis in Brebes Regency. This study used a case control design. The population consists of all people whose blood samples have been examined through a finger blood examination and recorded at the health center and Brebes District Health Office. The sample consisted of 32 patients with filariasis and 32 not sufferers of filariasis with the Purposive Sampling technique. The instruments used questionnaire and observation sheets. Data analysis used Chi-squared test and logistic regression test. The analysis shows that there is a correlation between resting place (p=0.000), breeding place (p=0.000), wire netting (p=0.002), the presence of livestock (p=0.015), knowledge (p=0.001), occupation (p=0.000), behaviour (p=0.024), and economic status (p=0.024) with the incidence of filariasis. The most dominant risk factors for obesity are work, resting place, and breeding place. The existence of a resting place and breeding place can increase the risk of filariasis so efforts are needed to maintain a clean and healthy environment.